Mapping the history of botanical collectors: spatial patterns, diversity, and uniqueness through time. Issue 1 (2nd January 2018) - Penn, Malcolm G.; Cafferty, Steve; Carine, Mark
Abstract : This study examines changing spatial patterns of botanical collections over a 400 year time frame, focussing on the collections at the Natural History Museum (BM) in comparison with global patterns. The Plant Collector Resource Database, which contains 68, 000 collector records was used to generate 250, 667 unique collector × country × date records. We observe an exponential increase in the number of collectors over time. The activities of collectors were investigated in 50-year time-slices from 1650–2000. We specifically considered the geographic scope of collections (i.e., countries in which collections were made), the depth of collections (i.e., the number of collectors per country) and the uniqueness of collections (i.e., the proportion not duplicated in other herbaria). Uniqueness was highest for the earliest time-slice. Collector activity is shown to be strongly influenced by extrinsic factors such as the development of trade and empire, which allowed for collections to expand in scope and depth, and conflicts, which reduced collecting activity. A striking finding concerns the uniqueness of collections through time. The considerable unique element of the collections in herbaria highlighted by this study provides a strong motivation for digitization efforts to ensure that collections are accessible to address key questions in systematics, biogeography, and ecology.